A análise da operação de aquisição da Gescartão, S.G.P.S., S.A. pela EUROPAC - Papeles y Cartones de Europa, S.A. - Luís, Nuno Miguel Rodrigues (2011)
The objective of the present study is to analyze the acquisition that occurred on 14th February 2005 in which Europac acquired a 50% stake in Imocapital. Europac is a vertically integrated company in the packaging sector dedicated to manufacturing paper, corrugated board and packaging to offer its customers the widest range of products as well as to the sale of electricity derived from its industrial activity. On 14th February 2005, Europac awarded a contract with Sonae to acquire a 50% stake in Imocapital, as well as a direct stake of 3.58% in Gescartão. This transaction, which acquisition price was EUR 97,866,760, increased Europac’s participation in Gescartão to 74.95% of capital. The acquisition was financed through a combined structure of equity (32.92 million euros) and debt (64.95 million euros). Gescartão acquisition’s rationale is supported by the acquisition of a more profitable company at a reasonable price and by the possibility of achieving operational and financial synergies. According with the estimates, this acquisition generated an economic value of 13 million euros showing that the amounts paid in Gescartão acquisitions represented a positive impact on the value creation process for Europac shareholders. The estimated Internal Rate Return is equivalent to 10.22%, which means that Gescartão investment was economically viable, remunerating the investment on Gescartão at a higher rate than the desired return by the shareholders (10.22% > Re).